EFEKTIVITAS PENGGUNAAN TEKNIK BISIK BERANTAI DALAM MENINGKATKAN KEMAMPUAN MENDENGAR - Syarif Alzulmi; Taufik Hidayat; Soraiya Usman (STKIP Subang, 2024)
The paralyzings of this research are: lack of teacher assistance and guidance in listening practice given how to teach and meet students, and less supportive environment in promoting listening skill given the teacher interview and student interview. This research aims to reveal the use and effectiveness of Bisik berantai technique to menigkatkan the listening skill of students in the eleventh grade at the Islamic State High School 9 East Jakarta. This research is quantitative research. And the research method is the experimental method. Empirical research is research that manipulates or controls natural states by creating artificial conditions. It was calculated by tests with one variable and one sample (Single T-Test). (Sig) (2 Tailed) for 0,000. Therefore, the magnitude level of 0.00 (Signifikansi) is less than 0.05 and then the result of tests with one variable and one sample (Single T-Test) has large results (Signifikan). That degree indicates that the alternative hypothesis (Ha) is